2023
DOI: 10.1136/bmjdrc-2022-003110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the prognostic performance of bedside tests used for peripheral arterial disease diagnosis in the prediction of diabetic foot ulcer healing

Abstract: IntroductionDiabetic foot ulceration (DFU) is a common and challenging complication of diabetes. Risk stratification can guide further management. We aim to evaluate the prognostic performance of bedside tests used for peripheral arterial disease (PAD) diagnosis to predict DFU healing.Research design and methodsTesting for Arterial Disease in Diabetes (TrEAD) was a prospective observational study comparing the diagnostic performance of commonly used tests for PAD diagnosis. We performed a secondary analysis as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The prevalence of peripheral neuropathy and PAD reported in this study are significantly greater than those recorded in the USA (6% and 9.5% respectively), possibly because of the lack of foot screening services in Zimbabwe [ 44 , 45 ]. Evidence of the impact of regular foot screening for reducing DF has been widely published, including in an Australian study that confirmed that non-indigenous people who frequently visited the clinic and received regular foot screening had a lower prevalence of DF than indigenous people who had poor health-seeking behaviours and limited resources in their community health facilities [ 30 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of peripheral neuropathy and PAD reported in this study are significantly greater than those recorded in the USA (6% and 9.5% respectively), possibly because of the lack of foot screening services in Zimbabwe [ 44 , 45 ]. Evidence of the impact of regular foot screening for reducing DF has been widely published, including in an Australian study that confirmed that non-indigenous people who frequently visited the clinic and received regular foot screening had a lower prevalence of DF than indigenous people who had poor health-seeking behaviours and limited resources in their community health facilities [ 30 , 46 ].…”
Section: Discussionmentioning
confidence: 99%